The circle without center. Modern, classical and vernacular tradition in the Visser House by Aldo van Eyck - García, Ana Rodríguez; Hernando de la Cuerda, Rafael (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
An extraordinary interest in the vernacular, the primitive and the popular went through post-war Europe in the 1950s. It is a period of great industrial development that will also show, probably by contrast, a revived interest in tradition. How to approach the dichotomy between industrial society and tradition is a central issue of the architectural debate of that time, carried out by architects born between wars, the Third Generation of the Modern Movement, and is the context of this text: an exploration on how tradition, and especially "the vernacular", influenced the proposals made by Aldo van Eyck (1918-1999), in his work of transferring to architecture what had already happened in the art of the avant-garde at the early twentieth century, and in science with the Theory of Relativity. Van Eyck presented at the last CIAM held at the Kröller Müller Museum, the Otterlo circles, a diagram formed by two circles that represent the interrelation, “the in-between”, between the three great traditions: classical, modern and vernacular. This paper delves deeper into the work carried out by Van Eyck, in the Visser House extension (1967-1969), developed as an interpretation in Holland of a "kiva" -the Pueblo Indians sacred place-, and a paradigmatic example of the interrelation mentionated.